The HIF‐PHI BAY 85‐3934 (Molidustat) Improves Anemia and Is Associated With Reduced Levels of Circulating FGF23 in a CKD Mouse Model. (10th March 2021) - Noonan, Megan L; Ni, Pu; Agoro, Rafiou; Sacks, Spencer A; Swallow, Elizabeth A; Wheeler, Jonathan A; Clinkenbeard, Erica L; Capitano, Maegan L; Prideaux, Matthew; Atkins, Gerald J; Thompson, William R; Allen, Matthew R; et al.
ABSTRACT: Fibroblast growth factor‐23 (FGF23) is a critical factor in chronic kidney disease (CKD), with elevated levels causing alterations in mineral metabolism and increased odds for mortality. Patients with CKD develop anemia as the kidneys progressively lose the ability to produce erythropoietin (EPO). Anemia is a potent driver of FGF23 secretion; therefore, a hypoxia‐inducible factor prolyl hydroxylase inhibitor (HIF‐PHI) currently in clinical trials to elevate endogenous EPO to resolve anemia was tested for effects on iron utilization and FGF23‐related parameters in a CKD mouse model. Mice were fed either a casein control diet or an adenine‐containing diet to induce CKD. The CKD mice had markedly elevated iFGF23 and blood urea nitrogen (BUN), hyperphosphatemia, and anemia. Cohorts of mice were then treated with a patient‐equivalent dose of BAY 85‐3934 (BAY; Molidustat), which elevated EPO and completely resolved aberrant complete blood counts (CBCs) in the CKD mice. iFGF23 was elevated in vehicle‐treated CKD mice (120‐fold), whereas circulating iFGF23 was significantly attenuated (>60%) in the BAY‐treated CKD mice. The BAY‐treated mice with CKD also had reduced BUN, but there was no effect on renal vitamin D metabolic enzyme expression. Consistent with increased EPO, bone marrow Erfe, Transferrin receptor (Tfrc), and EpoR mRNAs were increased in BAY‐treated CKD mice, and in vitro hypoxic marrow cultures increased FGF23 with direct EPO treatment. Liver Bmp‐6 and hepcidin expression were downregulated in all BAY‐treated groups. Femur trabecular parameters and cortical porosity were not worsened with BAY administration. In vitro, differentiated osteocyte‐like cells exposed to an iron chelator to simulate iron depletion/hypoxia increased FGF23; repletion with holo‐transferrin completely suppressed FGF23 and normalized Tfrc1. Collectively, these results support that resolving anemia using a HIF‐PHI during CKD was associated with lower BUN and reduced FGF23, potentially through direct restoration of iron utilization, thus providing modifiable outcomes beyond improving anemia for this patient population. © 2021 American Society for Bone and Mineral Research (ASBMR).